Julie Coleman. A History of Cant and Slang Dictionaries. Volumes I - IV. - Du Plessis, J.C.M.D. (Lexikos, 2014)
Reviews of:Julie Coleman. A History of Cant and Slang Dictionaries. Volume I: 1567–1784.Julie Coleman. A History of Cant and Slang Dictionaries. Volume II: 1785–1858.Julie Coleman. A History of Cant and Slang Dictionaries. Volume III: 1859–1936.Julie Coleman. A History of Cant and Slang Dictionaries. Volume IV: 1937–1984.